Making the Case for a Corpus-Driven, Translator-Oriented Glossary of Brazilian Colonial History - Candian, Selene (TradTerm, 2022)
This paper aims to investigate the possibility of thinking the nomenclature of the history of Brazil terminologically and, based on these terms and on equivalents already found by translators, of developing a corpus-driven, translator-oriented glossary of Brazilian colonial history. For that purpose, we have assembled two parallel corpora of works on the history of Brazil (Brasil: uma biografia / Brazil: a biography, by Lilia M. Schwarcz and Heloisa M. Starling, and História concisa do Brasil / A concise history of Brazil, by Boris Fausto), which have informed us, through a corpus-driven approach (Tagnin; Teixeira, 2012), potential candidate terms. We have chosen ten candidate terms and developed translator-oriented glossary entries based on an entry model adapted from Tagnin (2015).